Promoting Health Security In Hospital Dental Departments: An Evaluation Of Health Informatics Systems (The Review of Diabetic Studies, 2025)
This systematic assessment explores the pivotal role of health informatics for improving health security for dental departments offered in hospitals, specifically for emphasizing significant gaps present in the current design pattern of electronic medical records (EMR), concerning safety, integrity, and efficiency for patients. This thesis includes evidence-based research submitted by empirical evidence obtained from Indonesian hospitals as well as recently explored systematic studies on health informatics, identifying significant gaps available currently for security as well as format design for dental EMR. This thesis explores empirical evidence from both hospitals lacking significant designs such as odontogram design and lack of proper security for preventing data integrity as well as manipulation. Both aspects are critical for significant risk associated with unauthorized breach possibilities for healthcare as well as significant safety for forensic documentation for healthcare offered to dental patients. It can be explored clearly that current technological breakthroughs offered by significant aspects of advanced health informatics such as Artificial Intelligence, Blockchain Technology, Internet of Medical Things, as well as Cloud Computing, are revolutionary for emphasizing breakthrough approaches to counter identified gaps for completing design security for dental data, establishing immutable records, as well as emphasizing inviolable practices for information sharing for security. The crucial interpretive approach for the thesis explores that healthcare offered for dental departments can easily shift towards a revolutionary change by emphasizing significant approaches for designing more secure, efficient, as well as more emphasizing systems for healthcare concerning quality for dental departments offered for healthcare by hospitals.